Self-financing, parental transfer, and college education - LEE, Jungho (Institutional Knowledge at Singapore Management University, 2023)
We show that financial constraints can affect the human capital accumulation of college students by influencing students’ labor supply. We document that many college students work a substantial number of hours at low-skill jobs, and students who have fewer financial resources (in particular, parental transfer) tend to work more. We develop a model that incorporates college students’ labor supply and its interaction with parental transfer in the presence of financial constraints. By estimating the model, we quantify the trade-off between self-financing and human capital accumulation and discuss the implications of a wage subsidy policy.